2022
DOI: 10.3847/2041-8213/ac959e
|View full text |Cite
|
Sign up to set email alerts
|

Early Results from GLASS-JWST. IV. Spatially Resolved Metallicity in a Low-mass z ∼ 3 Galaxy with NIRISS*

Abstract: We report the first gas-phase metallicity map of a distant galaxy measured with the James Webb Space Telescope (JWST). We use the NIRISS slitless spectroscopy acquired by the GLASS Early Release Science program to spatially resolve the rest-frame optical nebular emission lines in a gravitationally lensed galaxy at z = 3.06 behind the A2744 galaxy cluster. This galaxy (dubbed GLASS-Zgrad1) has stellar mass ∼108.6 M ⊙, instantaneous star formation rate ∼8.6 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…We note that there are two companion galaxies in the same field that could be related to A2744-DSG-z3. The first one is a star-forming dwarf galaxy close to A2744-DSG-z3, denoted as GLASS-Z grad1 (Wang et al 2022). The angular offset is ≈3 1 on the image plane and then is delensed to ≈2″.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that there are two companion galaxies in the same field that could be related to A2744-DSG-z3. The first one is a star-forming dwarf galaxy close to A2744-DSG-z3, denoted as GLASS-Z grad1 (Wang et al 2022). The angular offset is ≈3 1 on the image plane and then is delensed to ≈2″.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Thanks to the JWST/NIRISS grism observations, the target close to A2744-DSG-z3 (GLASS-Zgrad1, recently reported in Wang et al 2022) is identified as one companion galaxy at the same redshift. The stellar mass of GLASS-Zgrad1 is ≈10 9 M e , and the delensed angular separation between the two sources is ≈2″, corresponding to 15.4 kpc at z = 3.06.…”
Section: Group Environment and The Formation Of Spiral-likementioning
confidence: 98%
See 1 more Smart Citation
“…We refer the reader to Roberts-Borsani et al (2022, Paper I of this series) and Vanzella et al (2022, Paper VII of this series) for GLASS-ERS studies that provide detailed discussion and utilization of gravitational lensing. In this study we only measure integrated line properties of galaxies and we refer the reader to Wang et al (2022, Paper IV of this series) for a GLASS-ERS study of spatially resolved emission line properties. Where applicable, we use H 0 = 70 km s −1 Mpc −1 , Ω m = 0.3, and Ω ∧ = 0.7.…”
Section: Introductionmentioning
confidence: 99%
“…We constrain jointly three key ISM properties: gas-phase metallicity (12+log(O/H)), nebular dust extinction (A N V ), and de-reddened Hβ flux ( f Hβ ), through the following likelihood function following Refs. 60,61 , i.e., L ∝ exp…”
Section: Methodsmentioning
confidence: 99%